FROM TRADITIONAL METHOD TO TASK-BASED APPROACH: A CRITICAL ANALYSIS OF FOREIGN LANGUAGE TEACHING METHODS - Labenko , Olha (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2023)
The new challenges prompt researchers to search for such approaches to teaching foreign languages that would ensure effective and rapid acquisition of a foreign language, contribute to the formation of a linguistic personality capable not only of communicating in all spheres, but also of successfully integrating into the society whose language is being studied. Successful mastering of foreign languages largely depends on the implementation of effective methods of teaching foreign languages, developed on the basis of modern linguistic theories.The article analyzes the advantages and disadvantages of the main methods of teaching foreign languages: traditional, direct, audio-lingual, audio-visual, communicative and task-based approach. The prerequisites for the emergence of these methods are considered, and their methodological principles are described. The development and improvement of foreign language teaching methods is associated with research in the field of linguistics, each new method was developed on the basis of a certain linguistic theory, taking into account the shortcomings of previous teaching methods.The traditional method focused mainly on the thorough study of grammar, vocabulary and processing of texts, but was not aimed at the development of communicative competence. Direct, audio-lingual, audio-visual and communicative methods focused mainly on the acquisition of oral speech. The task-based approach aims to form the skills necessary to perform certain actions using a foreign language.The peculiarities of the use of methods and techniques of these methods in the educational process are also investigated, and the possibilities of their implementation in the modern context of foreign language learning are considered. The combination of various optimal techniques and elements of these methods, depending on the purpose and context of learning, will ensure successful mastery of a foreign language at various levels._____________References:Bailly, N., Cohen, M. L’approche communicative, http://flenet.rediris.es/tourdetoile/ NBaillMCohenChomsky, Reflexions sur le langage: traduit de l’anglais (Flammarion, 1999), 49.Common European Framework of Reference for Languages (CEFR), Council of Europe, https://www.coe.int/en/web/common-european-framework-reference-languagesGermain, Le point sur l’approche communicative en didactique des langues // Centre éducatif et culturel (CEC), (Québec: Anjou, 1993), 129.Moirand, Enseigner à communiquer en langue étrangère ( Paris: Hachette, 1982), 192.Puren, Histoire des méthodologies d’enseignement des langues vivantes (Paris: Nathan-CLE international, 1988), 448.Riquois, Evolutions méthodologiques des manuels et matériels didactiques complémentaires en FLE, https://halshs.archives-ouvertes.fr/halshs-01066557RodriguezSeara,  L’évolution des méthodologies dans l’enseignement du français langue étrangère depuis la méthodologie traditionnelle jusqu’à nos jours, http://www.uned.es/ca-tudela/revista/n001/art_8.htm
Keywords: teaching method, traditional method, direct method, audio-lingual method, audio-visual method, communicative method, task-based approach